New Hirsutinolide-Type Sesquiterpenoids from Vernonia cinerea Inhibit Nitric Oxide Production in LPS-Stimulated RAW264.7 Cells - Kuo, Li-Ming Yang; Tseng, Pei-Yi; Lin, Yu-Chi; Liaw, Chia-Ching; Zhang, Li-Jie; Tsai, Keng-Chang; Lin, Zhi-Hu; Ho, Hsiu-O; Kuo, Yao-Haur (Planta Medica, 2018)
Phytochemical investigation of ethanol extracts from two Taiwanese collections of Vernonia cinerea resulted in the isolation of eighteen hirsutinolide-type sesquiterpenoids, including seven new ones designated as vernolides E – K (1–7). All structures were determined by a combination of detailed spectroscopic analyses (NMR and MS) and comparison with reported data. In an in vitro anti-inflammatory assay, compounds 3, 7, 9, 11, and 14 exhibited strong inhibitory activities toward NO production by LPS-induced RAW264.7 macrophages, with IC50 values of 1.18, 0.85, 0.66, 0.71 and 0.45 µM, respectively, without affecting cellular viability at 40 µM. Preliminary structure-activity relationships indicate that the ester groups at C-8 and C-13 may enhance inhibition of NO production.
Keywords: Vernonia cinerea; Asteraceae; hirsutinolide; vernolide; anti-inflammatory; RAW264.7 cells; nitric oxide